The Role of Internal Audit Quality in Reducing Creative Accounting Practices in Light of International Auditing Standards - ساعد بخوش , حسينة; بوطلاعة, محمد (Finance and Business Economies Review, 2021)
The study aimed to identify the impact of the quality of internal auditing in limiting creative accounting practices in light of international internal auditing standards from the point of view of practitioners of the profession of auditing and accounting in Algeria, and to achieve the objectives of the study, a questionnaire was designed based on similar previous literature. The study found that there is a positive and significant statistical impact of the quality of auditing in reducing creative accounting practices, and the quality of internal auditing in the absence of internal auditing standards affects massively compared to the application of internal auditing standards from the point of view of the vocabulary of the sample